Weathering the virtual storm: state boredom and coping strategies of novice and experienced Iranian EFL teachers in online learning - Masoomeh Estaji; Seyedeh Azadeh Sadr (BMC Psychology, 2025)
Abstract Emotions are an integral part of the classrooms, where learners and teachers constantly interact. Boredom, a negative academic emotion, adversely affects learning processes and achievement. As a result of its importance and essential role in EFL contexts, this area of inquiry has been the focus of academic research and critical examination. However, few studies (if any) have focused on EFL teachers’ coping strategies to ward off state boredom in online learning, considering their experience level. To fill this gap, the current study investigated the coping strategies of 237 novice and experienced Iranian EFL teachers with different experiences in online teaching contexts through the Coping with Boredom Scale (CBS) Questionnaire [1]. Besides, the authors delivered an open-ended questionnaire to 30 EFL teachers and conducted a semi-structured interview with 16 EFL teachers from the same sample. The results of the non-parametric Mann-Whitney U-Tests analysis indicated that novice and experienced teachers significantly differed in boredom coping strategies (p = .002) in that experienced teachers utilized a more comprehensive range of coping strategies to deal with their state boredom. The results of MAXQDA also evidenced that although there were some similarities in the utilized strategies across both groups, experienced teachers’ strategies were affected by their teaching experience, leading them to apply cognitive-avoidance strategies, like altering lesson plans and content, more frequently than novice teachers. The study presents practical implications for EFL teachers and researchers, stressing the role of teachers’ experiences in coping with boredom.